Generating Behaviors of Strong Tremors and Experimental Study of Rockburst-Triggering Criterion - Guifeng Wang; Feng Jin; Siyuan Gong; Linming Dou; Chaojun Fan; Wu Cai; Xiaoyuan Yuan (Shock and Vibration)
Numerous tremors occur during excavation and mining periods in coal mines, and low-energy tremors often occur before strong tremors. In addition, it is found that not all strong tremors cause rockbursts. Therefore, generating behaviors of strong tremors and the triggering criterion for the occurrence of the rockburst must be investigated. In this study, generating behaviors of strong tremors were inferred by velocity tomograms and energy density clouds. An innovative facility capable of applying dynamic disturbance to roadway models was developed to study the triggering criterion for rockbursts. Velocity tomograms indicated that the stress concentration extended to the syncline region with the advance of the coalface. High-energy-density clouds expanded rapidly and regularly in some areas that were parts of the high-velocity region, indicating that the stress increased rapidly in these areas, until strong tremors took place nearby. AE activities suggested that the modelled roadway offered good resistance as the dynamic loading energy grew from 29.4 J to 117.6 J. Then, sharp AE activity at the dynamic loading energy of 147 J indicated the ultimate shock resistance of the roadway was almost reached. Finally, bursting failure of the modelled roadway was observed at a dynamic loading energy of 176.4 J.